Differential Neuromuscular Adaptations to Skill-Integrated versus Sprint-Based HIIT: Implications for Match-Specific Performance in Racket Sports - Wismanadi, Himawan; Rusdiawan, Afif; Purnomo, Mochamad; Al Ardha, Muhammad Arif (Physical Education Theory and Methodology, 2026)
Background. Effective badminton performance requires sustaining a high level of physical effort while maintaining precise technical execution under fatigue. However, there is limited research comparing sprint-based high-intensity interval training (HIIT) and skill-integrated HIIT in terms of their physiological effects and transfer to match performance. HIIT is well established as an effective method for improving aerobic capacity and recovery. Objectives. This study aimed to examine the effects of sprint-based HIIT and skill-integrated HIIT on aerobic capacity, autonomic recovery, metabolic clearance, smash accuracy, and smash speed in trained badminton players. Materials and Methods. Thirty-six regional-level badminton players (aged 18–25 years) were stratified by age and baseline VO₂max and then randomly assigned to one of three groups: sprint-based HIIT (HSB; n = 12), skill-integrated HIIT (HSI; n = 12), or a control group (CON; n = 12). Both HIIT interventions followed an 8-week periodized program conducted three times per week, targeting 80–95% of maximal heart rate (HRmax). VO₂max was assessed using graded treadmill testing; heart rate recovery (HRR) was measured using Polar H10 monitors; and blood lactate concentration was determined using Accutrend Plus® analyzers at 5 and 10 minutes post-exercise. Smash accuracy was evaluated using a validated point-based target protocol, and smash speed was measured using radar. Data were analyzed using two-way repeated-measures ANOVA with Bonferroni post hoc corrections (p < 0.05). Effect sizes were calculated using Cohen’s d. Results. Both HSB and HSI groups demonstrated significant improvements in VO₂max (HSB: +6.7; HSI: +6.8 ml·kg⁻¹·min⁻¹, p < 0.001), HRR (HSB: +6.1; HSI: +6.5 bpm, p < 0.001), and metabolic clearance rate (p < 0.01), with effects exceeding those observed in the CON group (p < 0.05). Smash speed increased similarly in both HIIT groups (approximately +10 km/h, p < 0.001). However, HSI resulted in significantly greater improvements in smash accuracy compared to HSB (HSI: +8.1 vs. HSB: +4.7 points; p = 0.002), while the control group showed minimal changes across all variables. Conclusions. Both sprint-based and skill-integrated HIIT effectively enhance physiological parameters in badminton players; however, only skill-integrated HIIT leads to substantial improvements in technical performance. Therefore, integrating high-intensity training with sport-specific skill execution appears to be optimal for competitive readiness.